The Seagulls have Landed - Bateman, Colin (London Hodder Childern's Books, 2005)
Eddie and his gang are back, and they are in trouble when Eddie loses his Mum's baby. The gang is at hand to aid him though, and they will do their best to help their embattled leader, and find the baby. Suggested level: intermediate, junior secondary.
Keywords: Gangs -- Ireland